2019
DOI: 10.1016/j.ijhm.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The influence of customer-to-customer interactions on elderly consumers’ satisfaction and social well-being

Abstract: This study highlights the valuable role the hospitality industry can play in addressing a societal problem by studying how social interactions between elderly consumers and other customers influence the satisfaction and social well-being of the former. The data were collected from 268 elderly consumers in local coffee shops in the United Kingdom using a self-administrated questionnaire. The findings reveal that elderly customers' interactions with other customers have a direct effect both on customer satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 96 publications
(122 reference statements)
4
49
0
1
Order By: Relevance
“…This result confirmed previous findings that elderly consumers are most concerned about privacy protection (Nunan and Di Domenico, 2019). The relevance of social interaction among consumers has been acknowledged, particularly in reference to elderly reviewers (Altinay et al, 2019;Song et al, 2018). However, the findings of the present study showed that elderly guests were most concerned about their privacy during their hotel stays, indicating a need to investigate the balance between interaction and disclosure in this specific demographic group.…”
Section: Ijchmsupporting
confidence: 90%
“…This result confirmed previous findings that elderly consumers are most concerned about privacy protection (Nunan and Di Domenico, 2019). The relevance of social interaction among consumers has been acknowledged, particularly in reference to elderly reviewers (Altinay et al, 2019;Song et al, 2018). However, the findings of the present study showed that elderly guests were most concerned about their privacy during their hotel stays, indicating a need to investigate the balance between interaction and disclosure in this specific demographic group.…”
Section: Ijchmsupporting
confidence: 90%
“…In a study of online social support, a strong relationship was found between online peerto-peer support and patients' psychological well-being (Yao et al, 2015). However, numerous researchers posit that particular interactions may cause customers to influence peer customers more (Altinay et al, 2018;Song et al, 2018), which may provoke either a positive or an adverse experience (Wu, 2007) in commercial settings. For example, interaction such as a conversation taking place between customers can facilitate anxiety and boredom for dissatisfied customers (Harris and Baron, 2004).…”
Section: Social Interaction With Peersmentioning
confidence: 99%
“…However, consumer-to-consumer interaction does not stop here. To have a more comprehensive understanding of the purchased products or to confirm the existing purchase decisions again, it is a common behavior for consumers to continue to participate in interaction to further obtain relevant information and re-confirm purchase experience after purchasing in network communities [6].…”
Section: Introductionmentioning
confidence: 99%
“…There is a close relationship between consumer-to-consumer interaction and consumers' purchase behaviors [13]. Previous research has given little attention to consumer-to-consumer interaction' influence on dissatisfactory consumers' repetitive purchase, and the function of consumer knowledge and trust were not discussed [6,11,14]. Consumer knowledge is an important basis for consumers to choose and evaluate products.…”
Section: Introductionmentioning
confidence: 99%